GREEN WRITINGS OF ARUNDHATI ROY - Jose P., Jaison (Journal of Dharma, 2014)
This paper is an effort for an ecocritical reading of Arundhati Roy’s writings – the novel God of Small Things and a few of her non-fictional works with a focus on Broken Republic and The Algebra of Infinite Justice. Environmental concerns run parallel to, or are integrated with, other social and political implications in most of her writings. The paper identifies Roy as an environmental and literary activist who consistently stands for conservation along with her larger concerns of socio-political justice for the subaltern and she can be considered as an environmental justice activist. The paper also attempts to highlight the significance of environmentalism in literature against the backdrop of the enormous ecological threats that the planet earth faces at present.